Rust conversion and inhibition agent loaded nanosheet modified rust coating as well as preparation method and application of rust conversion and inhibition agent loaded nanosheet modified rust coating
By using boron nitride nanosheets loaded with strontium phytate in rust coatings, the problem of rust inhibitor diffusion failure is solved, and a long-term slow release of corrosion inhibitor is achieved, the corrosion protection performance of the coating is strengthened, and the service life of the rusted steel substrate is extended.
Patent Information
- Application Number
- CN202411823282.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The direct incorporation of rust inhibitors in existing rust coatings is poorly compatible with the coating, resulting in rust inhibitor diffusion failure and unable to effectively extend the service life of rust steel substrates.
The rust-containing coating modified with loaded rust-repressing agent nanosheets is used to add boron nitride nanosheets loaded with strontium phytate to the coating, and its chemical stability and physical barrier ability are used to form multiple synergies of barrier shielding, passivation stability, and chelation transformation.
It effectively avoids rapid leakage and failure of rust inhibitors, greatly extends the service life of the coating, and shortens the coating and maintenance cycle of rusted substrates.
Smart Images

Figure CN119775853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal anti-corrosion coating materials, and in particular to a rust-bearing coating modified by nanosheets loaded with rust-inhibiting agents, a preparation method and an application thereof. Background Art
[0002] Steel is the foundation of human industrial civilization, but it is also one of the main sources of carbon emissions. According to the World Steel Association, the average carbon emissions per ton of steel in the world is about 1.85 tons. According to statistics, nearly 1 / 4 of the total steel substrate produced in the world is corroded each year, and the direct economic losses caused by corrosion are about 700 billion US dollars. Therefore, the rational use of corroded steel substrates is the key to energy conservation and emission reduction, that is, the protection and life extension of corroded steel substrates have positive significance for energy conservation and emission reduction.
[0003] Applying rusty coatings is one of the most effective ways to reuse rusty steel substrates. The rust inhibitors in the coatings transform / inhibit the rusty steel substrates, slowing down the kinetic mechanism to inhibit further corrosion. However, the direct incorporation of rust inhibitors has poor compatibility with rusty coatings, and may cause failure problems such as excessive incorporation that accelerates corrosion and easy loss due to environmental effects, which is mainly attributed to the random free diffusion of rust inhibitors.
[0004] Therefore, how to construct a long-term slow release system of rust inhibitors to extend the service life of rusted steel substrates is lacking in the application of rust-resistant coatings to rusted steel substrates. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of diffusion failure of rust inhibitors, overcome the cumbersome rust removal process, thereby achieving long-term release of corrosion inhibitors, enhancing the corrosion protection performance of the coating, and forming an epoxy rust-resistant coating material that combines barrier shielding, passivation stabilization, and chelation conversion.
[0006] In order to achieve the above-mentioned object, the present invention provides a rust-bearing paint modified by rust-inhibiting agent nanosheets, including a paint system and a curing system; The coating system comprises, by mass, 30-50 parts of matrix coating, 0.1-5 parts of rust inhibitor nanosheets, 5-35 parts of anticorrosive filler, 0.5-3 parts of dispersant, 1-3 parts of defoamer, 0.5-5 parts of leveling agent, and 5-15 parts of diluent; The curing system comprises, by mass, 5-15 parts of a curing agent; The rust inhibitor-loaded nanosheets are boron nitride nanosheets loaded with strontium phytate.
[0007] It should be noted that in the present invention, the types of matrix coating, anticorrosive filler, dispersant, defoamer, leveling agent, diluent, and curing agent do not need to be strictly limited, and can be selected according to the conventional needs in the field. Exemplarily, the matrix coating can be selected from at least one of epoxy resin, polyacrylic resin, polyurethane resin, fluorocarbon resin, silicone resin, etc.; the anticorrosive filler can be at least one of barium sulfate, titanium dioxide, calcium carbonate, talcum powder, etc.; the dispersant can be at least one of anionic polymer compounds, polymer carboxylic acids, siloxane copolymers, etc.; the defoamer can be a polymer acrylate; the leveling agent can be a polyether-modified polysiloxane; the diluent can be at least one of xylene and n-butanol. Preferably, the matrix coating is selected as epoxy resin, and the corresponding curing agent is selected as a curing agent that matches the epoxy resin, such as polyamide, fatty amine, aromatic amine and other amine epoxy curing agents.
[0008] Furthermore, the method for preparing the boron nitride nanosheets loaded with strontium phytate comprises: Soluble strontium salt and phytic acid are dissolved in a solvent, and then boron nitride nanosheets are added and mixed, and then a solvothermal reaction is carried out to obtain boron nitride nanosheets loaded with strontium phytate.
[0009] Further, the molar ratio of the soluble strontium salt to phytic acid is 5-10:1; The mass ratio of the soluble strontium salt to the boron nitride nanosheets is 1-3:0.5-1.5; The mass volume ratio of the soluble strontium salt to the solvent is 2-10 g:50-150 mL. The type of the soluble strontium salt does not need to be strictly limited, and illustratively it can be at least one of strontium chloride, strontium nitrate, strontium acetate, etc.
[0010] Furthermore, the length of the boron nitride nanosheet is 3-30 μm, and the sheet thickness is 1-30 nm.
[0011] Furthermore, the solvent includes at least one of water, ethanol and acetone.
[0012] Furthermore, the solvent thermal reaction is maintained at 120-180° C. for 6-24 hours.
[0013] Furthermore, the curing system further comprises 0-3 parts by mass of an anti-flash rust agent.
[0014] The present invention also provides a method for preparing the above-mentioned rust-bearing paint modified by the rust-inhibiting agent-loaded nanosheets, which comprises, by weight, 30-50 parts of matrix coating, 5-35 parts of anticorrosive filler, 0.5-3 parts of dispersant, 1-3 parts of defoamer, 0.5-5 parts of leveling agent, and 5-15 parts of diluent are mixed and ground, and then 0.1-5 parts of rust-inhibiting agent nanosheets are added and continued to be mixed and ground to obtain a coating system, wherein the rust-inhibiting agent nanosheets are boron nitride nanosheets loaded with strontium phytate; The curing system composed of 5-15 parts of the curing agent is mixed with the coating system to obtain the rust-bearing coating modified by the rust-inhibiting agent nanosheets.
[0015] Furthermore, the curing system also includes 0-3 parts of an anti-flash rust agent.
[0016] The present invention also provides the application of the rust-bearing paint modified by the rust-inhibiting agent-loaded nanosheets in the field of metal corrosion protection.
[0017] The concept of the present invention is to add boron nitride nanosheets loaded with strontium phytate to the rust-resistant paint composition. Boron nitride nanosheets have excellent chemical stability and physical barrier ability. They set up mazes on the metal surface, extend the diffusion path of the corrosive medium, and slow down the occurrence of corrosion. At the same time, boron nitride also has good electrical insulation. When used for metal protection, it can prevent the transmission of electrons between the metal surface and the corrosive medium, thereby slowing down the corrosion rate of the metal. The molecular structure of strontium phytate contains multiple negatively charged phosphate groups, which can undergo a strong chelating reaction with the metal substrate to form a stable complex. In this process, strontium ions are released and adsorbed on the metal surface by physical adsorption to form an adsorption film. This film layer can prevent corrosive media such as oxygen and water from directly contacting the metal surface, thereby slowing down the corrosion rate of the metal. Boron nitride nanosheets loaded with strontium phytate have common advantages and improve the performance of rust-resistant paint.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adds boron nitride nanosheets loaded with strontium phytate to the tape embroidery coating system, which can avoid the problem of rapid leakage and failure caused by the rust inhibitor being directly added to the coating.
[0019] (2) The rust-resistant coating constructed by the present invention has multiple synergistic effects of barrier shielding, passivation stabilization, and chelation conversion, which greatly prolongs the service life of the coating and can shorten the coating and maintenance cycle of the rusted substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 shows a scanning electron microscope image of the boron nitride nanosheets used in Example 1; Figure 2 The scanning electron microscope image of the boron nitride nanosheet loaded with strontium phytate prepared in Example 1 is shown; Figure 3 A photograph of a test panel not coated with embroidery paint is shown; Figure 4 A photograph of the test plate with embroidery coating of coating Example 1 after 600 hours of neutral salt spray test is shown; Figure 5 The photo of the test plate with embroidery coating of the coating comparative example 1 after 600h neutral salt spray test is shown; Figure 6 A photograph of the test panel with embroidery paint of coating comparative example 2 after 600 hours of neutral salt spray test is shown. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0023] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] It should be noted that the boron nitride nanosheets in the examples and comparative examples are prepared by boron nitride ball milling, and have a length of about 25 μm and a sheet thickness of about 3 nm.
[0025] Example 1 A method for preparing a rust-bearing paint modified by nanosheets loaded with a rust inhibitor, comprising the following steps in parts by mass: Step (1) adding 2 parts of anionic polymer compound, 2 parts of polyether-modified polysiloxane, 3 parts of polymer acrylate, 20 parts of barium sulfate, 4 parts of xylene, and 6 parts of n-butanol to 50 parts of epoxy resin, mixing and grinding for 1 hour, then adding 2 parts of boron nitride nanosheets loaded with strontium phytate and continuing to mix and grind for 20 minutes, filtering with a 100-mesh sieve to obtain a coating system, and packaging for later use; Step (2) 6 parts of polyamide, 4 parts of fatty amine and 1 part of anti-flash rust agent are stirred and mixed to obtain a curing system; Step (3) uniformly mixes the coating system and the curing system to obtain a rust-bearing coating modified with rust-inhibiting agent nanosheets.
[0026] The preparation method of boron nitride nanosheets loaded with strontium phytate comprises: 4.76 g of strontium chloride (30 mmol) and 2.98 mL of 70% phytic acid (5 mmol) were dissolved in a beaker of 100 mL of deionized water, and then 4.96 g of boron nitride nanosheets were added and stirred evenly. The mixture was transferred to a polytetrafluoroethylene reactor and heated to 150 °C for hydrothermal reaction for 12 h. After the reaction, the mixture was naturally cooled to room temperature. The insoluble matter was collected and washed three times, dried at 60 °C for 24 h, and ground through a 100 mesh sieve to obtain boron nitride nanosheets loaded with strontium phytate.
[0027] Example 2 A method for preparing a rust-bearing paint modified by nanosheets loaded with a rust inhibitor, comprising the following steps in parts by mass: Step (1) adding 3 parts of anionic polymer compound, 3 parts of polyether-modified polysiloxane, 2 parts of polymer acrylate, 25 parts of barium sulfate, 8 parts of xylene, and 4 parts of n-butanol to 42 parts of epoxy resin, mixing and grinding for 1 hour, then adding 3 parts of boron nitride nanosheets loaded with strontium phytate and continuing to mix and grind for 20 minutes, filtering with a 100-mesh sieve to obtain a coating system, and packaging for later use; Step (2) 4 parts of polyamide, 4 parts of fatty amine and 2 parts of anti-flash rust agent are stirred and mixed to obtain a curing system; Step (3) uniformly mixes the coating system and the curing system to obtain a rust-bearing coating modified with rust-inhibiting agent nanosheets.
[0028] The preparation method of boron nitride nanosheets loaded with strontium phytate comprises: 7.14 g of strontium chloride (45 mmol) and 4.47 mL of 70% phytic acid (7.5 mmol) were dissolved in a beaker containing 100 mL of deionized water. Then, 4.96 g of boron nitride nanosheets were added and stirred evenly. The mixture was transferred to a polytetrafluoroethylene reactor and heated to 150 °C for hydrothermal reaction for 12 h. After the reaction, the mixture was naturally cooled to room temperature. The insoluble matter was collected and washed three times. The mixture was dried at 60 °C for 24 h and ground through a 200 mesh sieve to obtain boron nitride nanosheets loaded with strontium phytate.
[0029] Example 3 A method for preparing a rust-bearing paint modified by nanosheets loaded with a rust inhibitor, comprising the following steps in parts by mass: Step (1) adding 3 parts of anionic polymer compound, 3 parts of polyether-modified polysiloxane, 2 parts of polymer acrylate, 23 parts of barium sulfate, 5 parts of xylene, and 8 parts of n-butanol to 45 parts of epoxy resin, mixing and grinding for 1 hour, then adding 1 part of boron nitride nanosheets loaded with strontium phytate and continuing to mix and grind for 20 minutes, filtering with a 100-mesh sieve to obtain a coating system, and packaging for later use; Step (2) 4 parts of polyamide, 5 parts of fatty amine and 2 parts of anti-flash rust agent are stirred and mixed to obtain a curing system; Step (3) uniformly mixes the coating system and the curing system to obtain a rust-bearing coating modified with rust-inhibiting agent nanosheets.
[0030] The preparation method of boron nitride nanosheets loaded with strontium phytate comprises: 7.14 g of strontium chloride (45 mmol) and 4.47 mL of 70% phytic acid (7.5 mmol) were dissolved in a beaker containing 100 mL of deionized water. Then, 2.48 g of boron nitride nanosheets were added and stirred evenly. The mixture was transferred to a polytetrafluoroethylene reactor and heated to 150 °C for hydrothermal reaction for 12 h. After the reaction, the mixture was naturally cooled to room temperature. The insoluble matter was collected and washed three times. The mixture was dried at 60 °C for 24 h and ground through a 200 mesh sieve to obtain boron nitride nanosheets loaded with strontium phytate.
[0031] Example 4 The method is basically the same as Example 1, except that no flash rust inhibitor is added in step (2).
[0032] Example 5 The method is basically the same as Example 1, except that in the preparation method of boron nitride nanosheets loaded with strontium phytate, the amounts of strontium chloride and phytic acid used are 25 mmol and 5 mmol, respectively.
[0033] Example 6 The method is basically the same as Example 1, except that in the preparation method of boron nitride nanosheets loaded with strontium phytate, the amounts of strontium chloride and phytic acid used are 50 mmol and 5 mmol, respectively.
[0034] Comparative Example 1 A method for preparing a rust-resistant coating modified by boron nitride nanosheets comprises the following steps in parts by mass: Step (1) adding 3 parts of anionic polymer compound, 3 parts of polyether modified polysiloxane, 2 parts of polymer acrylate, 25 parts of barium sulfate, 8 parts of xylene and 4 parts of n-butanol to 42 parts of epoxy resin, mixing and grinding for 1 hour, then adding 3 parts of boron nitride nanosheets and continuing to mix and grind for 20 minutes, filtering with a 100-mesh sieve to obtain a coating system, and packaging for later use; Step (2) 4 parts of polyamide, 4 parts of fatty amine and 2 parts of anti-flash rust agent are stirred and mixed to obtain a curing system; Step (3) uniformly mixes the coating system and the curing system to obtain a rust-resistant coating modified by boron nitride nanosheets.
[0035] Comparative Example 2 A method for preparing a rust-bearing coating modified by strontium phytate comprises the following steps in parts by mass: Step (1) adding 3 parts of anionic polymer compound, 3 parts of polyether-modified polysiloxane, 2 parts of polymer acrylate, 25 parts of barium sulfate, 8 parts of xylene, and 4 parts of n-butanol to 42 parts of epoxy resin, mixing and grinding for 1 hour, then adding 3 parts of strontium phytate and continuing to mix and grind for 20 minutes, filtering with a 100-mesh sieve to obtain a coating system, and packaging for later use; Step (2) 4 parts of polyamide, 4 parts of fatty amine and 2 parts of anti-flash rust agent are stirred and mixed to obtain a curing system; Step (3) uniformly mixes the coating system and the curing system to obtain a rust-resistant coating modified with strontium phytate.
[0036] The preparation method of strontium phytate is the same as that in Example 1 and will not be described in detail here.
[0037] The microscopic morphologies of the boron nitride nanosheets used in Example 1 and the prepared boron nitride nanosheets loaded with strontium phytate were observed using a scanning electron microscope. The results are as follows: Figure 1 and Figure 2 As shown. It can be seen that the boron nitride nanosheets present a block structure formed by the stacking of sheets; at the same time, the boron nitride nanosheets loaded with strontium phytate have some small particles accumulated on the surface of the boron nitride nanosheets compared with the boron nitride nanosheets, which indicates that strontium phytate is successfully loaded on the surface of the boron nitride nanosheets through a simple one-step hydrothermal reaction.
[0038] Refer to the standard HG / T 5173-2017 Water-based primer for rust-resistant coatings. Hot-rolled steel plates were used as test objects. After sandblasting, salt spray test, and wet heat test, the floating rust on the steel plate was manually removed with a wire brush. The firmly attached rust was retained and dried. The floating dust on the surface was blown off with high-pressure air to obtain the following Figure 3 The test plate shown in the figure was then immediately coated with the tape embroidery coating prepared in the examples and comparative examples, and the prepared plate was kept in neutral salt spray for 600 hours, and the morphology was observed. The photographs of the test plates prepared with the tape embroidery coating prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown in the figure below. Figure 4 , Figure 5 and Figure 6 As shown. It can be seen that the rust-resistant coating modified by boron nitride nanosheets in comparative example 1 and the rust-resistant coating modified by strontium phytate in comparative example 2 both showed red rust on the coating surface, while the rust-resistant coating modified by rust-resistant nanosheets loaded in Example 1 showed no obvious rust and blistering on the coating surface. This shows that compared with boron nitride nanosheets, boron nitride nanosheets loaded with strontium phytate have better corrosion resistance. The rust-resistant coatings of Examples 4-6 were also tested, and the results were similar to those of Example 1, and all had good rust-resistant and rust-resistant corrosion resistance.
[0039] The reason why the embroidery coating of the present invention has excellent rust-removing and rust-inhibiting performance is that: boron nitride nanosheets have excellent chemical stability and physical barrier ability, and set up mazes on the metal surface to extend the diffusion path of the corrosive medium and slow down the occurrence of corrosion; at the same time, boron nitride also has good electrical insulation. When used for metal protection, it can prevent the transmission of electrons between the metal surface and the corrosive medium, thereby slowing down the corrosion rate of the metal. The molecular structure of strontium phytate contains multiple negatively charged phosphate groups, which can undergo a strong chelating reaction with the metal substrate to form a stable complex. In this process, strontium ions are released and adsorbed on the metal surface by physical adsorption to form an adsorption film. This film layer can prevent corrosive media such as oxygen and water from directly contacting the metal surface, thereby slowing down the corrosion rate of the metal. However, when using boron nitride or strontium phytate alone as a rust inhibitor, the coating is easily deactivated due to the poor compatibility of boron nitride with the coating matrix. At the same time, under the same test, the coating with only strontium phytate added is more severely corroded, which indicates that strontium phytate cannot have a long-term effect due to the premature release of phosphate. Boron nitride nanosheets loaded with strontium phytate have common advantages. Strontium phytate and boron nitride play a good synergistic role, so that the boron nitride nanosheets loaded with strontium phytate are well dispersed in the coating, inhibiting the premature release of active groups in strontium phytate, thereby improving the performance of the embroidery coating.
[0040] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A rust-resistant paint modified by nanosheets loaded with rust inhibitor, characterized in that: Including coating system and curing system; The coating system comprises, by mass, 30-50 parts of matrix coating, 0.1-5 parts of rust inhibitor nanosheets, 5-35 parts of anticorrosive filler, 0.5-3 parts of dispersant, 1-3 parts of defoamer, 0.5-5 parts of leveling agent, and 5-15 parts of diluent; The curing system comprises, by mass, 5-15 parts of a curing agent; The rust inhibitor-loaded nanosheets are boron nitride nanosheets loaded with strontium phytate.
2. The rust-bearing paint modified by rust-inhibiting agent nanosheets according to claim 1, characterized in that: The method for preparing the boron nitride nanosheets loaded with strontium phytate comprises: Soluble strontium salt and phytic acid are dissolved in a solvent, and then boron nitride nanosheets are added and mixed, and then a solvothermal reaction is carried out to obtain boron nitride nanosheets loaded with strontium phytate.
3. The rust-bearing paint modified by rust-inhibiting agent nanosheets according to claim 2, characterized in that: The molar ratio of the soluble strontium salt to phytic acid is 5-10:1; The mass ratio of the soluble strontium salt to the boron nitride nanosheets is 1-3:0.5-1.5; The mass volume ratio of the soluble strontium salt to the solvent is 2-10 g:50-150 mL.
4. The rust-bearing paint modified by rust-inhibiting agent nanosheets according to claim 2, characterized in that: The length of the boron nitride is 3-30 μm, and the thickness of the sheet is 1-30 nm.
5. The rust-bearing paint modified by rust-inhibiting agent nanosheets according to claim 2, characterized in that: The solvent includes at least one of water, ethanol and acetone.
6. The rust-bearing paint modified by rust-inhibiting agent nanosheets according to claim 2, characterized in that: The solvothermal reaction is maintained at 120-180° C. for 6-24 hours.
7. The rust-bearing paint modified by rust-inhibiting agent nanosheets according to claim 1, characterized in that: The curing system further comprises 0-3 parts by weight of an anti-flash rust agent.
8. A method for preparing a rust-bearing coating modified by nanosheets loaded with a rust inhibitor, characterized in that: In parts by mass, it includes: 30-50 parts of matrix coating, 5-35 parts of anticorrosive filler, 0.5-3 parts of dispersant, 1-3 parts of defoamer, 0.5-5 parts of leveling agent, and 5-15 parts of diluent are mixed and ground, and then 0.1-5 parts of rust-inhibiting agent nanosheets are added and continued to be mixed and ground to obtain a coating system, wherein the rust-inhibiting agent nanosheets are boron nitride nanosheets loaded with strontium phytate; The curing system composed of 5-15 parts of the curing agent is mixed with the coating system to obtain the rust-bearing coating modified by the rust-inhibiting agent nanosheets.
9. The method for preparing the rust-bearing paint modified by the rust-inhibiting agent nanosheets according to claim 8, characterized in that: The curing system also includes 0-3 parts of an anti-flash rust agent.
10. Use of the rust-bearing paint modified by the rust inhibitor nanosheets loaded as claimed in any one of claims 1 to 7 in the field of metal corrosion protection.
Citation Information
Patent Citations
Preparation methods of metal surface treatment agent containing nano boron nitride and corrosion-resistant coating
CN106010181A
BN-loaded TiO2-SrTiO3 heterojunction photocatalytic degradation material and preparation method thereof
CN113289658A
Flame-retardant smoke-suppressing polylactic acid fiber and preparation method thereof
CN114855298A
Zinc phosphate composite treated steel panel
JP2001179873A
Organic composite coated steel panel excellent in solvent resistance
JP2001199003A